Mindfulness‐based interventions for adults who are overweight or obese: a meta‐analysis of physical and psychological health outcomes. (11th November 2016) - Rogers, Jeffrey M.; Ferrari, Madeleine; Mosely, Kylie; Lang, Cathryne P.; Brennan, Leah
Summary: Objective: The aim of this study was to evaluate the impact of mindfulness‐based interventions on psychological and physical health outcomes in adults who are overweight or obese. Methods: We searched 14 electronic databases for randomized controlled trials and prospective cohort studies that met eligibility criteria. Comprehensive Meta‐analysis software was used to compute the effect size estimate Hedge's g. Results: Fifteen studies measuring post‐treatment outcomes of mindfulness‐based interventions in 560 individuals were identified. The average weight loss was 4.2 kg. Overall effects were large for improving eating behaviours ( g  = 1.08), medium for depression ( g  = 0.64), anxiety ( g  = 0.62) and eating attitudes ( g  = 0.57) and s mall for body mass index (BMI; g  = 0.47) and metacognition ( g  = 0.38) outcomes. Therapeutic effects for BMI ( g  = 0.43), anxiety ( g  = 0.53), eating attitudes ( g  = 0.48) and eating behaviours ( g  = 0.53) remained significant when examining results from higher quality randomized control trials alone. There was no efficacy advantage for studies exceeding the median dose of 12 h of face‐to‐face intervention. Studies utilizing an Acceptance and Commitment Therapy approach provided the only significant effect for improving BMI (g = 0.66), while mindfulness approaches produced great variation from small to large ( g  = 0.30–1.68) effects across a range of psychological health and eating‐related constructs. Finally, the limited longitudinal data suggested maintenance of BMI ( g  = 0.85) and eating attitudes ( g  = 0.75) gains at follow‐up were only detectable in lower quality prospective cohort studies. Conclusions: Mindfulness‐based interventions may be both physically and psychologically beneficial for adults who are overweight or obese, but further high‐quality research examining the mechanisms of action are encouraged.